Landscape Diversity: Multiple-Use Landscapes for Reclaimed Phosphatic Clay Areas - Edward A. Hanlon (EDIS)
The intent of this document is to explore the benefits of using reclaimed phosphatic clay areas — a result of phosphate mining in central Florida — for multiple purposes to add to the local economy and the sustainability of the community and to take advantage of the clay resource for environmental and agricultural purposes. This document is written as a concept paper, which integrates information learned about phosphatic clay. This document is SL 229, a fact sheet of the Soil and Water Science Department, UF/IFAS Extension. Original publication date September 2005.